Ecotourism Promotional Strategy: Domestic Tourists' Intention-To-Revisit Model in Kerinci District, Jambi, Indonesia - Prihatno, Joko (2003)
Studies on intention-to-revisit is important in understanding consumers' (tourists') behavior in relation to their decision to revisit a tourism destination. To determine the factors which influence a tourist's intention to visit an area more than once, a model of intention-to-revisit an ecotourism destination in Kerinci- Jambi was developed and tested using path analysis. The results of the study indicate that domestic tourists' intention-to-revisit are significantly influence by their accessibility to information sources (from professional advice, advertisement, and other-tourism support), the variety of information sources, tourists' perception, satisfaction, image of the destination, and tourists' preference, simultaneously. The results provided an important tool for the application of an intention-to-revisit model in developing an ecotourism promotional strategy in Kerinci District, particularly, the combination of the promotional components, namely; publicity, advertisements, and personal selling. Kerinci District attracted a target market of domestic tourists with an average age of 24 years and a monthly average income of US $80. These domestic tourists observed that Kerinci District has strengths in product characteristics based on nature, serenity, and historical/cultural attractions. Hence, Kerinci is appropriate to be promoted as an integrated ecotourism destination with core attractions that include Kerinci Seblat National Park, complimentary attractions that include Kerinci Lake Festival , and supporting attractions that include features surrounding the park. The analysis on the effectiveness of the existing promotional programs indicated that the variety of information sources had the highest effect on domestic tourists' intention-to-revisit. The level of accessibility to information sources from other-tourism-support had the second effect on domestic tourists' intention-to-revisit, followed by professional advice, and advertisement which has the lowest effect. A model of domestic tourists' intention-to-revisit a destination could be used to develop ecotourism promotional strategy in Kerinci District, Jambi, Indonesia.